mRNA Vaccine: How to Meet the Challenge of SARS-CoV-2 - Jin, Yingqi; Hou, Chen; Li, Yonghao; Zheng, Kang; Wang, Chuan (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with high infectivity, pathogenicity and variability, is a global pandemic that has heavy damage on public health and world economy. The development of safe and effective vaccines is crucial to the prevention and control of the epidemic. As an emerging vaccine, mRNA vaccine is widely used in antiviral and anti-infectious treatments, and has significant safety, efficacy and high production. It has received support and funding from many pharmaceutical enterprises and become one of the main technologies for preventing COVID-19. This review introduces the current status of SARS-CoV-2, focus on the challenges of developing mRNA vaccine against SARS-CoV-2 and discusses the relevant strategies.